Shrouds and footprints in Robert Morris - Corrain, Lucia (E|C, 2020)
This contribution addresses the issue of Enunciation in the context of contemporary arts through the examination of two series of works created in 2015 and 2017 by the American artist Robert Morris (1934-2018).